Yield and Yield Contributing Attributes Of Potato as Influenced by Vermicompost And Seed Tuber Size (SAARC Journal of Agriculture, 2021)
Low yield is crucial bottleneck for potato production in Bangladesh. The application of vermicompost may enhance the yield of potato. The experiment was consisted of two factors, i.e., Factor A: - Vermicompost level (Vm1-4): Vm1: 0 t ha-1, Vm2: 3 t ha-1, Vm3: 6 t ha-1 and Vm4: 9 t ha-1; Factor B:- Tuber size (T1-5): T1: 5-10 g, T2: 10-20 g, T3: 20-30 g, T4: 30-40 g and T5: > 40 g. The experiment was conducted in a split-plot design with three replications. Vermicompost had significant effect on most of the yield contributing parameters investigated under present study. Results revealed that yield parameters increased with increasing vermicompost level irrespective of tuber size. Among the twenty (20) treatment combinations, vermicompost at the rate of 9 t ha-1 with tuber size > 40 g produced the maximum yield (31.33 t ha-1) that was 53.53 % higher than that of control with 3273.01 $ of monetary advantage. Therefore, present study suggests that potato growers may use vermicompost for increasing yield of potato in Bangladesh.SAARC J. Agric., 19(1): 71-79 (2021)